PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MENENTUKAN IDE POKOK PARAGRAF SISWA KELAS V SD NEGERI 003 PULAU KOPUNG KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Yuwanda Megri Santika; Otang Kurniaman; Zariul Antosa (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Reading is one of the important aspects of the communication process. Reading can make someone better understand the contents of the reading. In learning to make it easier for students to understand the contents of the reading it will be easier if it begins with the ability to determine the main ideas of the paragraph. Based on this, the researchers conducted a study by applying the Cooperative Integrated Reading and Composition (CIRC) learning model to the ability to determine the main idea of paragraphs in fifth-grade students of SD Negeri 003 Pulau Kopung. This study aims to determine the effect of the CIRC learning model on the ability to determine the main ideas of paragraphs of fifth-grade students of SD Negeri 003 Pulau Kopung. This research method is a quasi-experimental Nonequivalent Control Group Design. This study was conducted in two classes, namely the VA class as the control class and VB class as the experimental class with 22 students in each class. The results of the study showed that the CIRC learning model influenced the ability determine the main idea of the paragraph with the results of calculations sourced from the index gain, the experimental class using the CIRC learning model gets an increase in gain of 0.59 with the middle class and the control class with the ordinary learning model gets an increase of 0.31 with the middle class.